Soft material heat conductivity test clamp for heat reflection test technology

By designing a fixture that includes a quartz dish, a quartz plate, and a heating chip, the complexity and universality issues of thermal conductivity testing for soft matter materials are solved, enabling rapid and economical thermal conductivity testing. This fixture is suitable for in-situ temperature change and high-temperature aging detection of liquid and organic materials.

CN121049334APending Publication Date: 2025-12-02CHINA ELECTRONICS RELIABILITY AND ENVIRONMENTAL TESTING INSTITUTE ((THE FIFTH INSTITUTE OF ELECTRONICS MINISTRY OF INDUSTRY AND INFORMATION TECHNOLOGY) (CHINA SAIBAO LABORATORY)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511231267.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-30
Publication Date
2025-12-02

AI Technical Summary

Technical Problem

Existing technologies are difficult to apply directly to the thermal conductivity testing of soft materials such as liquids, gels, and pastes. They also cannot detect changes in thermal conductivity and high-temperature aging processes at different temperatures in situ. The operation is complex, inefficient, and lacks universality and economy.

Method used

A fixture comprising a lower quartz dish, an upper quartz plate, a U-shaped fixing frame, and a heating chip was designed. Through magnetic adsorption and low thermal resistance welding technology, the thermal conductivity of soft materials can be tested. The heating chip is integrated for in-situ testing of thermal conductivity changes at different temperatures and high-temperature aging processes.

Benefits of technology

It enables rapid, efficient, and low-cost testing of the thermal conductivity of soft matter materials. The fixture is reusable, unaffected by the material being tested, and suitable for milligram-level samples, offering greater versatility and cost-effectiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121049334A_ABST
    Figure CN121049334A_ABST
Patent Text Reader

Abstract

The invention provides a soft material thermal conductivity test fixture for a heat reflection test technology, and relates to the technical field of packaging material testing, the soft material thermal conductivity test fixture comprises a lower quartz vessel, the top surface is provided with a groove structure for accommodating a soft material sample, and the four corners of the bottom surface are provided with blind holes and embedded with columnar magnets; an aluminum film is arranged on the bottom surface of the upper-layer quartz plate; a strip-shaped magnet is embedded in the inner side of the concentric-square-shaped fixing frame, and the strip-shaped magnet presses the upper-layer quartz plate above the groove body structure of the lower-layer quartz vessel through the magnetic adsorption effect; the heating chip is fixed on the bottom surface of the lower-layer quartz vessel through an arranged welding layer and is opposite to the position of the groove body structure; the thermal conductivity testing device can be used for testing the thermal conductivity of a soft material, meanwhile, the heating chip is integrated, the thermal conductivity change conditions of a sample at different temperatures can be tested in situ, and the thermal conductivity of the sample can be detected in situ in a high-temperature aging state. And a degradation process of material thermal conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of packaging material testing technology, and more particularly to a test fixture for the thermal conductivity of soft matter materials for thermal reflection testing technology. Background Technology

[0002] Time-domain and frequency-domain thermal reflectance testing is a key material thermophysical parameter testing technique developed based on the fundamental principle that "the reflectivity coefficient of a material to probe light changes with temperature." This technique detects changes in the reflectivity of a sample surface using visible light, indirectly sensing temperature changes on the object's surface, and then analyzes the heat transfer process within the material, ultimately determining core thermophysical parameters such as the material's thermal diffusivity and thermal conductivity. With its advantages of rapid and efficient measurement and small sample requirements, this technique has been widely applied in the field of materials science.

[0003] However, existing technical solutions are mainly applicable to the thermal conductivity testing of solid samples such as inorganic and metallic materials. The testing process usually requires the sample to have nanoscale surface flatness. The conventional method is to deposit a thin film of the sample under test on the surface of a substrate with good thermal conductivity using a coating technique; at the same time, a sensing layer made of a metallic material with high reflectivity to visible light, such as aluminum or platinum, needs to be prepared on the surface of the sample under test to enhance the detection sensitivity of the reflectivity signal.

[0004] The aforementioned technical requirements make it difficult to directly apply existing technologies to the thermal conductivity testing of soft materials such as liquids, gels, and pastes (e.g., organic polymers, liquid crystals, liquid metals). Although some materials can be pre-treated to form thin films before coating and testing, this method requires repeated adjustments to coating process parameters for different materials to obtain a smooth sample. Each test requires repeating the tedious sample preparation process, which is not only complex and inefficient but also lacks universality and economy, severely limiting the widespread application of time-domain and frequency-domain thermal reflectance testing technologies in the field of thermal property testing of soft materials.

[0005] Furthermore, existing technologies can only perform thermal conductivity testing at a single temperature, and cannot detect changes in the thermal conductivity of materials under different temperature conditions in situ, nor can they simulate actual service scenarios such as high-temperature aging. As a result, they cannot meet the requirements for thermal property characterization of soft materials under complex working conditions.

[0006] Therefore, it is necessary to provide a test fixture for the thermal conductivity of soft matter materials for thermal reflection testing technology to solve the above-mentioned technical problems. Summary of the Invention

[0007] To address the aforementioned technical problems, this invention provides a thermal conductivity testing fixture for soft matter materials, designed for thermal reflection testing technology. This fixture can be used to test the thermal conductivity of soft matter materials. It also integrates a heating chip, enabling in-situ testing of thermal conductivity changes in samples at different temperatures, as well as in-situ detection of the degradation process of material thermal conductivity under high-temperature aging conditions.

[0008] This invention provides a testing fixture for the thermal conductivity of soft matter materials for thermal reflection testing technology, comprising:

[0009] The lower quartz dish has a groove structure on its top surface for holding soft material samples, and blind holes with embedded columnar magnets at the four corners of its bottom surface.

[0010] The upper quartz sheet has an aluminum film on its bottom surface;

[0011] A U-shaped fixing frame has a bar magnet embedded in its inner side. The bar magnet presses the upper quartz sheet onto the groove structure of the lower quartz dish through magnetic adsorption.

[0012] The heating chip is fixed to the bottom surface of the lower quartz dish by a set solder layer and is directly opposite to the position of the tank structure. The heating chip is provided with a back gold layer.

[0013] The bottom surface of the lower quartz dish is provided with a metal aluminum layer, and the welding layer is located between the metal aluminum layer and the back gold layer of the heating chip.

[0014] Preferably, the trough structure is a square trough.

[0015] Preferably, the heating chip includes:

[0016] Alumina substrate;

[0017] A heating resistor circuit layer disposed on the front side of an alumina substrate;

[0018] The insulating layer area covering the heating resistor circuit layer;

[0019] A gold backing layer is disposed on the back side of an alumina substrate.

[0020] Preferably, the cross-section of the loop-shaped fixing frame is L-shaped, and the inner side of the frame has bar magnets continuously distributed along the circumference of the loop-shaped frame.

[0021] Preferably, the aluminum film is a magnetron sputtered aluminum film.

[0022] Preferably, the welding layer comprises welding silver paste.

[0023] Preferably, the back gold layer is a sputtered gold layer or a sputtered copper layer.

[0024] Preferably, the depth of the blind hole in the lower quartz dish is greater than the height of the columnar magnet, and the opening of the blind hole is filled with epoxy resin.

[0025] Compared with related technologies, the thermal conductivity testing fixture for soft matter materials provided by this invention for thermal reflection testing technology has the following advantages:

[0026] The fixture of this invention can be used for rapid, efficient, and low-cost testing of the thermal conductivity of such materials. This makes the testing of thermal properties of organic and liquid materials based on time-domain thermal reflectance testing technology more convenient and simple. Furthermore, the use of the testing fixture eliminates the need for sample preparation via spin coating or vacuum evaporation, the fixture is reusable, and unaffected by the material being tested, thus making it more economical and universally applicable. Moreover, the testing process requires only milligram-level samples, which is more sample-efficient compared to laser scattering and steady-state heat flow methods. Attached Figure Description

[0027] Figure 1 This is a schematic diagram of the fixture of the present invention;

[0028] Figure 2 This is a schematic diagram of the heating chip of the present invention;

[0029] Figure 3 This is a schematic diagram of the structure of the loop-shaped fixing frame of the present invention;

[0030] The diagram is labeled as follows: 1. Upper quartz plate; 2. Aluminum film; 3. Lower quartz dish; 4. Columnar magnet; 5. Epoxy resin; 6. Metallic aluminum layer; 7. Welding layer; 8. Heating chip; 9. Back gold layer; 10. U-shaped fixing frame; 11. Bar magnet; 12. Heating resistor circuit layer; 13. Insulation layer area; 14. Alumina substrate layer. Detailed Implementation

[0031] The present invention will now be described in further detail with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and not intended to limit it. Furthermore, it should be noted that, for ease of description, only the parts relevant to the invention are shown in the drawings, not all structures. Moreover, unless otherwise specified, the embodiments and features described herein can be combined with each other.

[0032] A thermal conductivity testing fixture for soft matter materials, compatible with time-domain thermal reflectance testing and reflectivity thermal imaging testing technologies, is disclosed. It can be used to test liquid and soft matter materials such as polymers, liquid crystal materials, liquid metals, and high-boiling-point liquids. The fixture enables the evaluation of material thermal conductivity using a time-domain thermal reflectance testing platform, as well as the evaluation of material thermal conductivity at different temperatures.

[0033] This fixture enables rapid, efficient, and low-cost testing of the thermal conductivity of such materials. It makes the testing of thermal properties of organic and liquid materials based on time-domain thermal reflectance measurement technology more convenient and simpler. Furthermore, the use of this fixture eliminates the need for sample preparation via spin coating or vacuum evaporation. The fixture is reusable and unaffected by the material being tested, making it more economical and universally applicable. It is also worth noting that the testing process requires only milligram-level samples, which is more sample-efficient than laser scattering and steady-state heat flow methods.

[0034] refer to Figures 1 to 3 As shown, the fixture is generally divided into an upper quartz plate, a lower quartz dish, a heating chip, and a U-shaped fixing frame. Figure 1 This is a fixture design drawing. The left side shows an analytical diagram of the fixture structure, and the right side shows the overall design drawing of the assembled fixture. 1 is the upper quartz plate coated with aluminum film 2; 3 is the lower quartz dish with a groove structure; 4 is a columnar magnet installed in the lower quartz dish; 5 is epoxy resin used for sealing. In the top and bottom views of the lower quartz dish, the columnar magnets 4 are distributed at the four corners of the back of the lower quartz dish 3, and the sample groove is in the center of the front view of the lower quartz dish 3. 6 is the aluminum layer on the back of the quartz dish; 8 is the heating chip; 9 is the back gold layer on the back of the bottom heating chip; 7 is the welding layer between the lower quartz dish and the heating chip. 10 is a U-shaped fixing frame, and 11 is a bar magnet installed in the fixing frame.

[0035] Figure 2 This is a schematic diagram of the specific structure of the heating chip 8. Figure 2 In the diagram, 13 is the insulating layer region of polyimide, 12 is the heating resistor circuit layer of serpentine Pt, 14 is the aluminum oxide substrate layer of the chip, and 10 is the back gold layer.

[0036] Figure 3 This is a structural diagram of a U-shaped fixing frame. The left image is the interface view, the middle image is the front view, and the right image is the top view of the rear. 10 represents the U-shaped fixing frame, and 11 represents the embedded bar magnet.

[0037] More specifically:

[0038] The lower quartz dish 3 has a groove structure on its top surface for holding soft material samples, and blind holes with embedded columnar magnets 4 at the four corners of its bottom surface. The depth of the blind holes in the lower quartz dish 3 is greater than the height of the columnar magnets 4, and the opening of the blind holes is filled with epoxy resin 5.

[0039] The upper quartz plate 1 has an aluminum film 2 on its bottom surface.

[0040] The U-shaped fixing frame 10 has a bar magnet 11 embedded in its inner side. The bar magnet 11 presses the upper quartz sheet 1 onto the groove structure of the lower quartz dish 3 through magnetic adsorption. The cross-section of the U-shaped fixing frame 10 is L-shaped, and the bar magnets 11 are continuously distributed along the circumference of the U-shaped frame.

[0041] The heating chip 8 is fixed to the bottom surface of the lower quartz dish 3 by a welding layer 7, and is directly opposite to the position of the tank structure. The heating chip 8 is provided with a back gold layer 9. More specifically, the heating chip 8 includes:

[0042] Alumina substrate layer 14;

[0043] Heating resistor circuit layer 12 is disposed on the front side of alumina substrate layer 14;

[0044] Insulation layer region 13 covering the heating resistor circuit layer 12;

[0045] A back gold layer 9 is disposed on the back side of the alumina substrate 14.

[0046] The bottom surface of the lower quartz dish 3 is provided with a metal aluminum layer 6, and the welding layer 7 is located between the metal aluminum layer 6 and the back gold layer 9 of the heating chip 8.

[0047] The fixture is fabricated from two pieces of high-transmittance quartz glass. One piece is made of thicker quartz glass, with a square groove structure in the middle of the glass with a depth ranging from 200nm to 500nm. Blind holes are also machined at the back edge to accommodate columnar magnets 4. A heating chip 8 is fixed to the back of the upper quartz glass 1 using a low thermal resistance soldering method. The other piece of quartz glass is coated with a 100nm thick aluminum film 2 by magnetron sputtering. During testing, the upper quartz glass 1 with the aluminum film 2 is placed on top of the aforementioned lower quartz dish 3. A U-shaped metal strip containing magnets is pressed against the stacked quartz dishes on the outside. The test system is then used to perform tests under visible light laser of a specific wavelength and pulse frequency.

[0048] During the test, the soft material to be tested is directly added or spread into the lower quartz dish 3, and then slowly covered with the upper quartz plate 1 coated with aluminum. It is then fixed with a U-shaped fixing frame 10, and the test can be performed. For organic materials requiring thermosetting or photocuring, thermosetting or UV curing can be performed after the material to be tested is filled. This method allows difficult-to-process soft material samples or liquid samples to be stored in a thin space between the two quartz materials, ensuring a flat contact between the aluminum film 2 detector layer and the material to be tested, meeting the detection requirements of time-domain thermal reflectometry. The heating chip 8 on the back directly contacts the sample cell through low thermal resistance welding, enabling precise temperature control of the sample.

[0049] In practice, the design and fabrication of a thermal testing fixture for soft matter materials for thermal reflectivity testing technology mainly includes the following key steps:

[0050] The first step is the processing of the upper quartz plate 1 and the lower quartz dish 3, specifically as follows:

[0051] A quartz glass plate measuring 2cm × 2cm × 1mm (length × width × thickness) is selected. After ultrasonic cleaning and plasma cleaning, a 100mm thick aluminum film 2 is prepared using magnetic control to obtain the upper quartz plate 1. Then, a quartz glass plate measuring 2cm × 2cm × 5mm (length × width × thickness) is selected. After ultrasonic cleaning, a positive-direction mask with a 1cm × 1cm (length × width) window area and a side length ≥ 2cm is used to cover the quartz plate. A square groove with a depth of approximately 200nm (or 300-500nm, controlled within the range of hundreds of nanometers) is etched using plasma etching technology. Simultaneously, blind holes with a diameter of 3mm and a depth of 4mm are machined at the four corners on the back of the quartz plate using mechanical drilling. These holes are filled with 3mm diameter, 3.5mm long columnar magnets 4, and finally, the blind holes are sealed with epoxy potting compound.

[0052] Secondly, the processing of the U-shaped fixing frame 10 includes:

[0053] A U-shaped metal frame with an inner side length of 1.8cm, an outer side length of 2.1cm, a thickness of 0.5mm, and an overall height of 5mm is fabricated using stainless steel or aluminum. The cross-section of the metal frame is L-shaped. A strip magnet with a length of 1.8cm, a width of 0.2cm, and a height of 0.2cm is fixed to the inside of the metal frame using epoxy resin 5. This results in the outer U-shaped fixing frame 10.

[0054] Next is the fabrication and fixation of the heating chip 8, which specifically includes:

[0055] The heating chip 8 is fabricated on an alumina substrate with a thickness of 0.5 mm using magnetron sputtering with a linewidth of micrometers. Then, a high-temperature resistant polyimide insulating layer is coated on the surface using screen printing. Finally, a 500 nm thick back gold layer 9 is fabricated on the back of the heating chip 8 using magnetron sputtering.

[0056] Finally, the heating chip 8 is installed with low thermal resistance, which specifically includes:

[0057] To ensure low thermal resistance mounting of the heating chip 8, a layer of aluminum (or gold, copper, silver, or other metals) is sputtered onto the back of the lower quartz dish 3 with the help of a template, followed by a layer of soldering silver paste. Then, the gold layer 9 of the heating chip 8 is placed over the silver paste and soldered at a temperature of around 200°C. This allows the heating chip 8 to be fixed to the back of the lower quartz dish with low thermal resistance, ensuring uniform heating of the material during testing and rapid temperature response of the material properties.

[0058] Based on the principle of time-domain thermal reflectance testing, this invention uses quartz material to process a test sample loading vessel that can be used to test soft matter materials and liquid materials. Furthermore, a heating chip is bonded to this vessel through a low thermal resistance welding process, thereby expanding it into a soft matter material testing fixture that can test the thermal conductivity of soft matter materials in situ.

[0059] The low thermal resistance welding technology involves designing a back metal layer on the back of the bottom quartz dish and the back of the heating chip, and then using high thermal conductivity silver paste to achieve low thermal resistance welding between the chip and the quartz dish.

[0060] By utilizing the wetting effect of soft matter and liquid materials on metal surfaces, an atomically smooth test interface can be constructed.

[0061] It should also be noted that the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus. Unless otherwise specified, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes that element.

Claims

1. A fixture for testing the thermal conductivity of soft matter materials for thermal reflection testing technology, characterized in that, include: The lower quartz dish (3) has a groove structure on its top surface for holding soft material samples, and blind holes with embedded columnar magnets (4) at the four corners of its bottom surface. The upper quartz sheet (1) has an aluminum film (2) on its bottom surface; A U-shaped fixing frame (10) has a bar magnet (11) embedded in its inner side. The bar magnet (11) presses the upper quartz sheet (1) onto the groove structure of the lower quartz dish (3) through magnetic adsorption. The heating chip (8) is fixed to the bottom surface of the lower quartz dish (3) by a welding layer (7) and is directly opposite to the position of the tank structure. The heating chip (8) is provided with a back gold layer (9). The bottom surface of the lower quartz dish (3) is provided with a metal aluminum layer (6), and the welding layer (7) is located between the metal aluminum layer (6) and the back gold layer (9) of the heating chip (8).

2. The thermal conductivity testing fixture for soft matter materials according to claim 1, characterized in that, The trough structure is a square trough.

3. A thermal conductivity testing fixture for soft matter materials according to claim 2, characterized in that, The heating chip (8) includes: Alumina substrate (14); A heating resistor circuit layer (12) is disposed on the front side of the alumina substrate layer (14); Insulation layer area (13) covering the heating resistor circuit layer (12); A back gold layer (9) is disposed on the back side of the alumina substrate (14).

4. A thermal conductivity testing fixture for soft matter materials according to claim 3, characterized in that, The cross-section of the loop-shaped fixing frame (10) is L-shaped, and the inner bar magnets (11) are continuously distributed along the circumference of the loop-shaped frame.

5. A thermal conductivity testing fixture for soft matter materials according to claim 4, characterized in that, The aluminum film (2) is a magnetron sputtered aluminum film.

6. A thermal conductivity testing fixture for soft matter materials according to claim 5, characterized in that, The welding layer (7) contains welding silver paste.

7. A thermal conductivity testing fixture for soft matter materials according to claim 6, characterized in that, The back gold layer (9) is a sputtered gold layer or a sputtered copper layer.

8. A thermal conductivity testing fixture for soft matter materials according to claim 7, characterized in that, The depth of the blind hole in the lower quartz dish (3) is greater than the height of the columnar magnet (4), and the opening of the blind hole is filled with epoxy resin (5).